Penyuluhan Kesehatan Melalui Pemeriksaan Gula Darah di Kecamatan Mancak Menuju Masyarakat Sehat - Ade Ariesmayana (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2020)
Health and education are the most important things for the progress of the nation. If one of them does not go well, the progress of a nation will be hampered, the extension activities carried out in Mancak District are carried out so that the public is aware of the importance of the meaning of health. The examination is carried out for free by checking blood sugar levels because Indonesia is the country with the highest diabetics in the world. The method used is free examinations and free consultation with a doctor, after checking blood sugar levels to get direction from medical experts. The results obtained are that there are some whose blood sugar levels are not normal because of an unhealthy lifestyle, smoking and lack of physical activity.